PERSEPSI UMAT HINDU TERHADAP AJARAN DANA PUNIA DALAM KITAB BHAGAWAD GITA DI DESA DUDA TIMUR KECAMATAN SELAT KABUPATEN KARANGASEM - I Gede Adnyana; I Nyoman Sueca; I Nyoman Alit Supandi (UHN IGB Sugriwa Denpasar, 2020)
Dana punia are a sacred activity as one of the applications of dharma teachings. For that reason, it is also important to know how the primacy of the dana punia teachings in Hindu literature is especially in the Bhagawad Gita. Hinduism awareness, especially Hindus in Duda Timur Village, Selat District, Karangasem District, on the teachings of dana Punia in the Bgagawad Gita book will be able to provide benefits in life as human beings who are obliged to dana punia or offer everything good to God, humans and the environment. sincerely.The problems that will be discussed include (1) What are the dana punia teachings in the Book of Bhagawad Gita? (2) What is the public perception of the dana punia teachings in the Book of Bhagawad Gita? (3) What is the actualization of the dana punia in the Bhagawad Gita? This study aims to find out (1) the teaching of dana punia in the Bhagawad Gita Book. (2) Public perception of the dana punia teachings in the Bhagawad Gita book. (3) Actualization of dana punia teachings in the Bhagawad Gita book.The theory used is the theory of Hermeneutics, Perception, and Symbolic Interactionism. The subjects of this study were community leaders, data collection methods used were observation, interviews, document studies, and library studies. The collected data was analyzed by qualitative descriptive analysis method with steps of reduction, presentation of data and conclusion.The results showed: dana punia teachings in Hindu literature, types of dana punia in the Bhagawad Gita book, implementation of dana punia in East Duda Village, forms of dana punia, proceeds from the implementation of dana punia, impacts resulting from the implementation of dana punia, and actualization of teachings dana punia in the Bhagawad Gita book.